Comprehensive Identification of HD-Zip Family Genes in Coix lacryma-jobi L. and Their Potential Roles in Response to Abiotic Stress - Yongle Wang; Hongjuan Wang; Xianyong Lu; Chun Yu; Benli Jiang; Jiabao Zhu; Yujiao Wang (Plants)
HD-Zip (homeodomain-leucine zipper) transcription factors play a crucial role in plant growth, development, and stress response; however, the HD-Zip gene family of Coix lacryma-jobi L. has not been identified. In this study, a total of 40 HD-Zip gene family members were identified in the genome of Coix. According to phylogenetic analysis, the Coix HD-Zip gene was divided into four subfamilies (I–IV), of which the HD-Zip I subfamily can be further divided into five branches. Moreover, HD-Zip members of the same subfamily usually share similar gene structures and conserved motifs. The transcription factor binding site enrichment analysis showed that there are many motifs for binding with transcription factors such as ERF (Ethylene responsive factor), MYB (v-myb avian myeloblastosis viral oncogene homolog), and ARF (Auxin Response Factor) in the promoter region of the ClHDZ genes. The results of qPCR (Quantitative Polymerase Chain Reaction) and expression profile analysis showed that ClHD-Zip I genes showed different levels of expression under different stress treatments. Among them, ClHDZ4 was located in the nucleus, and its expression pattern was significantly upregulated under salt, drought, and high-temperature stress. In addition, ectopic expression of ClHDZ4 enhanced the growth of yeast strains under drought, salt, or high-temperature treatment. In summary, these results laid a foundation for further research on the resistance function of the Coix HD-Zip gene.